Intensity of artefacts in cone beam CT examinations caused by titanium and glass fibre-reinforced composite implants - Niina Kuusisto; Sisko Huumonen; Antti Kotiaho; Marianne Haapea; Jami Rekola; Pekka Vallittu (British Institute of Radiology, 2022)
Objectives:
The aim was to compare titanium and glass fibre-reinforced composite (FRC) orbital floor implants using cone beam CT (CBCT). FRC implants are nonmetallic and these implants have not been analysed in CBCT images before. The purpose of this study is to compare the artefact formation of the titanium and the FRC orbital floor implants in CBCT images.
Methods:
One commercially pure titanium and one S-glass FRC with bioactive glass particles implant were imaged with CBCT using the same imaging values (80 kV, 1 mA, FOV 60 × 60 mm). CBCT images were analysed in axial slices from three areas to determine the magnitude of the artefacts in the vicinity of the implants. Quantified results based on the gray values of images were analysed using analysis-of-variance.
Results:
Compared to the reference the gray values of the titanium implant are more negative in every region of interest in all slices (p < 0.05) whereas the gray values of the FRC implant differ statistically significantly in less than half of the examined areas.
Conclusions:
The titanium implant caused artefacts in all of the analysed CBCT slices. Compared to the reference the gray values of the FRC implant changed only slightly and this feature enables to use wider imaging options postoperatively.